Pengaruh Motivasi dan Disiplin Terhadap Kinerja Dengan Komitmen Organisasional Sebagai Variabel Intervening Pada Pegawai: Pada Pegawai Kantor Kesyahbandaran dan Otoritas Pelabuhan Kelas II Jayapura - Morin, Oktovina Olga; Wambrauw, Oscar O.; Syauta, Jack H. (Adhigana Papua: Jurnal Ilmiah Magister Manajemen, 2024)
This study aims to determine and analyze the influence of competency variables, work motivation and discipline that have an impact on the performance of assistants in the Department of Industry, Trade, Cooperatives and SMEs in Jayapura City. The sample unit in this study is a staff of 42 employees, taken using purposive sampling technique. Data analysis used descriptive statistics and Multiple Regression Analysis. The results showed that (1). Simultaneously, the variables of competence, work motivation, and discipline have a significant positive impact on the performance of assistants but are significant (2). Partially, the competence variable has a positive and significant effect, however, motivation has a positive and significant effect and the discipline variable has a positive and significant effect on the performance of the assistants (3). The variable of work motivation dominantly has a significant effect on the performance of the assistant staff.